Cybersecurity games for secure programming education in the industry: gameplay analysis - Gasiba, Tiago (2020)
To minimize the possibility of introducing vulnerabilities in source code, software developers may attend security awareness and secure coding training. From the various approaches of how to raise awareness and adherence to coding standards, one promising novel approach is Cybersecurity Challenges. However, in an industrial setting, time is a precious resource, and, therefore, one needs to understand how to optimize the gaming experience of Cybersecurity Challenges and the eﬀect of this game on secure coding skills. This work identiﬁes the time spent solving challenges of diﬀerent categories, analyzes gaming strategies in terms of a slow and fast team proﬁle, and relates these proﬁles to the game success. First results indicate that the slow strategy is more successful than the fast approach. The authors also analyze the possible implications in the design and the training of secure coding in an industrial setting by means of Cybersecurity Challenges. This work concludes with a brief overview of its limitations and next steps in the study.